Dietary Prevention of Atopic March in Pediatric Subjects With Cow's Milk Allergy - Carucci, Laura; Nocerino, Rita; Paparo, Lorella; Di Scala, Carmen; Berni Canani, Roberto (Frontiers in Pediatrics, 2020)
Cow’s milk allergy (CMA) is one of the most common food allergies and the most expensive allergic diseases in the pediatric age. There is no cure for CMA, and actual disease management of CMA is based on strict avoidance of cow milk proteins-containing foods, access to rescue medication and use of substitutive formulas. Early life CMA could be one of the first steps of the “allergic march” (AM), leading to the occurrence of other atopic manifestations later in the life, including asthma and oculorhinitis, with subsequent further increase of costs for health care systems and families of affected children. In the last years, diet is emerged as a relevant strategy to prevent allergic diseases through the active long-lasting modulation of the immune system mediated, at least in part, by epigenetic mechanisms. We provide an overview of studies that investigate the potential role of different dietary strategies in preventing the AM in pediatric patients with CMA.